Female students’ participation in physical activities in Oman - Al Bakri, Khadija (2019)
The rising number of inactivity-related health problems for individuals and society is a critical concern in today’s world. This applies also too many students who are at risk of low levels of physical activity. The purpose of this study is to investigate the factors that affect physical activity participation of female university students in Oman. The participation of female students in physical activity percentage in Oman raises a health concern as a very few students are physically active for different reasons such as, time, lack of sport facilities, family support and self-motivation to be physical active. Sultan Qaboos University (SQU) was chosen as the setting for this study, because it is the only university with a full sport facility for females only, and it is accessible to all student free of charge. Literature review was conducted on the barriers that affect and or motivate female students’ physical activity in Oman and the Arab world. Studies have shown that female students experience many different obstacles to participate in physical activity. These include lack of time, society and culture influence, lack of financial income, body image, safety, lack of support, lack of appropriate educational system and facilities. The main aims and objectives of this study are based on two basic components: firstly, to identify the barriers that prevent the students from being physical activity and the secondly to study what are the motives that motivate them to be and continue being physically active. Through a qualitative research approach, six interviews took place with students from Sultan Qaboos University to gain a perspective on the current situation of the students’ physical activity participation. After the interviews were transcribed and translated the data was analyzed by dividing it down into broader sections. The researcher sorted and selected the data based on the questions ask and the similarity of the answers to gain a comprehensive insights into the phenomena that is being explored and to find key patterns, themes and issues in the data. The main results of this thesis revealed that the most popular exercises among university students is walking as its convenient and it’s an easy access. Future research should include male students and students from different ages to investigate the similarities and differences within the group, continued research should be conducted with other private colleges and universities to broaden the study to different educational sectors